Manajemen Keamanan Lingkungan di Panti Jompo Salib Putih Terhadap Risiko Jatuh Pada Lansia - Dhanang Puspita; David Nakka Gasong; Harvian Charisma Bangngu (Indonesian Journal of Nursing Research (IJNR), 2018)
In the elderly, there is a period of decline in some aspects, related to declining inpsychological, social, and physical conditions. Effects of reduction physical condition, elderly are sensitive to some degenerative diseases. The nursing homeisan old residence that is voluntarily or submitted by the family to be taking care of the needs of which management can be done by government and private. Falling is the incident not realized by someone sitting on the floor or on the ground orinalower place. In Indonesia, from 115 nursing home resident as much as 30 elderly or around 43.47% who has a fall incident. Purpose this research is to know safety management in the nursing home of Salib Putih to risk of fall in elderly. The method this research used is a qualitative research method with a descriptive approach. The way of choosing the subject is done by Purpose Sampling. Data completion technique in this research is by way of in-depth interview. The results of data analysis in this research, obtained 3 themes related to environmental safety management of incident in elderly at Salib Putih Nursing home, i.e.:Â  Falling Causes in Elderly, Nursing home Environmental Setting to avoid falls in elderly, and the role of housing board nursing home to minimizing the risk of falling in elderly. The conclussion is still a lack of environmental safety management at Salib Putih Salatiga Nursing Home to the risk of falling in the elderly. The causes from the thing are lack of supervision of housing board nursing home. In addition to environmental management at Salib Putih nursing home, it hasn't fully fill standardization of nursing home in general, so it still causes accidents to the elderly.